Catecholamines as central modulators of the stress response. A preliminary study in Atlantic salmon (Salmo salar) head kidney cells - Madaro, Angelico; Basso, Victoria Warth; Olsen, Rolf Erik (Frontiers in Fish Science, 2025)
This study investigated the contribution of catecholamines to stress regulation in Atlantic salmon, with the goal of clarifying inconsistencies between the classical model of cortisol control in teleosts and recent observations that challenge it. According to the traditional theory, cortisol secretion is driven primarily by adrenocorticotropic hormone (ACTH) through activation of the hypothalamic–pituitary–interrenal (HPI) axis. However, several studies in salmonids have reported that elevations in cortisol can occur in the absence of, or prior to, measurable increases in ACTH. To examine whether catecholamines influence cortisol production we performed ex vivo incubations of head kidney tissue either with ACTH (10−6 M, 10−8 M, and 10−10 M), or catecholamine (adrenaline and noradrenaline, 10−6 M, 10−8 M for both) and monitored cortisol production up to 60 min post-incubation. The results confirmed that ACTH elicited a cortisol response, but not catecholamines. However, when head kidneys were incubated with combinations of ACTH (10−6 M) and catecholamines (adrenaline or noradrenaline, 10−7 M each) there was a massive increase in cortisol (by ~2.4-fold) production far exceeding that of ACTH alone. These findings suggest that catecholamines are unlikely to function as independent stimulators of cortisol synthesis but will enhance the responsiveness or sensitivity of interrenal cells to ACTH. Such a synergistic interaction could represent an adaptive mechanism enabling rapid cortisol elevation during acute stress, thereby helping to reconcile discrepancies between ACTH and cortisol profiles reported in vivo. Overall, this work provides new insight into the interplay between sympathetic activation and endocrine regulation in teleost fish.